WHEN IS IDENTITY STRONGER : FIRST MATERIAL EVIDENCE OF COLONIAL JEWISH COMMUNITY IN BUENOS AIRES - Schávelzon, Daniel (2013)
For the first time in Buenos Aires we had find material evidence of the practice of the Jewish religion during the colonial period. The finding of a tile floor engraved on its underside with a Star of David, from a colonial upper class house, introduced us on the field of the situation of the Jewish population in the Spanish colonial world.